Uso do dispositivo sonoro individual e suas implicações no sistema vestibulococlear - Mello, Anelise Spencer de (2019)
This research aimed to characterize the use of the individual sound device in the context of recreational noise and to verify its implications on the vestibulocochlear system in young adults, comparing the results obtained with those of non-users of the device, and preparing graphic material in order to perform educational action as a preventive approach. This is a cross-sectional, observational, comparative and descriptive research that used a quantitative method. The final sample was consisted of 72 subjects aged to 18 and 35 years, which 48 were users of the individual sound device and 24 were non-users. Subjects were separated into study group and control group and test results were compared between subjects. The mean age of the groups was 21.5 years and 22.9 years, respectively. The study group was composed of 19 women and 29 men and the control group by 18 women and six men. They were submitted to audiological evaluation, by means of Pure Tone Audiometry, Logoaudiometry and Immitanciometry, to meet the inclusion and exclusion criteria, as well as High Frequency Audiometry, Evoked Otoacoustic Emissions and Cervical Vestibular Evoked Myogenic Potential to meet the research objectives. For statistical analysis, the ensuing nonparametric tests were used: Mann-Whitney U test, Kruskal- Wallis, followed by multiple comparisons, and Spearman correlation test. The sample was characterized by the use of the individual sound device for a period longer than three and up to ten years, for more than one hour daily, more than two days a week, at an intensity exceeding 60% of the maximum capacity of the equipment, as well as greater preference to insertion earphones. Among the subjective implications, were found auditory and extra-auditory complaints in the study group, with predominance of speech comprehension difficulty and concentration and tiredness, respectively. As objective implications, there were more absent responses in otoacoustic emissions in the study group, in addition to statistically significant differences in at least one frequency per ear and predominantly lowered signal-to-noise ratio values compared to the control group. At high frequency audiometry, lower thresholds were observed in the study group, although they did not differ statistically. When comparing sound intensity categories, differences in specific frequencies were also observed between the groups studied. In the cervical vestibular evoked myogenic potential, a difference was found only in P13 amplitude in the right ear; however, the absolute values of amplitude and inter-amplitude were reduced in the right ear of the study group and higher in the same group in the left ear. A positive correlation was found in P13 amplitude with time of use in years, but in the comparison by sound intensity categories and time of use in years, no statistically significant differences were observed. Finally, graphic material was developed to support the individual educational action, with a preventive focus on the use of the individual sound device and applied to all research subjects. It was concluded that the indiscriminate use of individual sound devices in the recreational context, can lead to negative implications on the vestibulocochlear system, which can be verified early, through complementary evaluations, in order to prevent future auditory and vestibular alterations.